In vitro antiviral activity of medicinal mushroom Ganoderma neo-japonicum Imazeki against enteroviruses that caused hand, foot and mouth disease - W.X, Ang; S., Sarasvathy; U.R., Kuppusamy; V., Sabaratnam; S.H., Tan; K.T., Wong; David, Perera; K.C., Ong (The Malaysian Society of Parasitology and Tropical Medicine (MSPTM), 2021)
Hand, foot and mouth disease (HFMD) is a highly contagious viral disease that predominantly affects children younger than 5 years old. HFMD is primarily caused by enterovirus A71 (EVA71) and coxsackievirus A16 (CV-A16). However, coxsackievirus A10 (CV-A10) and coxsackievirus A6 (CV-A6) are being increasingly reported as the predominant causative of HFMD outbreaks worldwide since the past decade. To date, there are still no licensed multivalent vaccines or antiviral drugs targeting enteroviruses that cause HFMD, despite HFMD outbreaks are still being frequently reported, especially in Asia-Pacific countries. The high rate of transmission, morbidity and potential neurological complications of HFMD is indeed making the development of broad-spectrum antiviral drugs/agents against these enteroviruses a compelling need. In this study, we have investigated the in vitro antiviral effect of 4 Ganoderma neo-japonicum Imazeki (GNJI) crude extracts (S1-S4) against EV-A71, CV-A16, CV-A10 and CV-A6. GNJI is a medicinal mushroom that can be found growing saprophytically on decaying bamboo clumps in Malaysian forests. The antiviral effects of this medicinal mushroom were determined using cytopathic inhibition and virus titration assays. The S2 (1.25 mg/ml) hot aqueous extract demonstrated the highest broad-spectrum antiviral activity against all tested enteroviruses in human primary oral fibroblast cells. Replication of EV-A71, CV-A16 and CVA10 were effectively inhibited at 2 hours post-infection (hpi) to 72 hpi, except for CV-A6 which was only at 2 hpi. S2 also has virucidal activity against EV-A71. Polysaccharides isolated and purified from crude hot aqueous extract demonstrated similar antiviral activity as S2, suggesting that polysaccharides could be one of the active compounds responsible for the antiviral activity shown by S2. To our knowledge, this study demonstrates for the first time the ability of GNJI to inhibit enterovirus infection and replication. Thus, GNJI is potential to be further developed as an antiviral agent against enteroviruses that caused HFMD.